A family-group name correction in Aves: Tachurisidae instead of Tachurididae Ohlson, Irestedt, Ericson & Fjeldså, 2013 - Franz, Ismael (Zootaxa, 2015)
The genus Tachuris Lafresnaye, 1836 was recently placed in a new monotypic family rank taxon, Tachurididae Ohlson, Irestedt, Ericson & Fjeldså, 2013, proposed to reflect the molecular recovery of this taxon as an independent lineage related to Tyrannidae Vigors, 1825 and Rhynchocyclidae Berlepsch, 1907 (Ohlson et al. 2013). The purpose of this paper is to propose a correction in the original spelling of the family name Tachurididae used by Ohlson et al. (2013) to agree with the rulings of the International Code of Zoological Nomenclature (ICZN 1999; hereafter “Code”), taking account of the complex etymology of the name.